Ecodesign Enhancement of Polymeric Resins: Reinforcing with Synthetic and Natural Fibers Using Theory of Inventive Problem Solving-Algorithm of Inventive Problem Solving for Sustainable Composite Design - Dobrotă, Dan; Icociu, Cristina Vasilica; Lazăr, Sergiu; Racz, Sever-Gabriel; Moraru, Gina-Maria (Polymers, 2024)
This study examines the enhancement of the mechanical strength of polymer resins through reinforcement with synthetic (glass) and natural (hemp, jute) fibers, using the TRIZ-ARIZ methodology to optimize composite design for improved mechanical properties, sustainability, and economic efficiency. Mechanical testing, thermogravimetric analysis (TGA), and scanning electron microscopy (SEM) were conducted to evaluate the properties of the composite materials. Regarding tensile strength testing, the results showed the following: jute fiber achieved the best results, with a maximum tensile values of 43.75 MPa (partial reinforcement) and 43.53 MPa (complete reinforcement); glass fiber recorded maximum tensile values of 34.55 MPa (partial reinforcement) and 34.52 MPa (complete reinforcement); and hemp fiber yielded maximum tensile values of 24.98 MPa (partial reinforcement) and 24.86 MPa (complete reinforcement). The mechanical performance of partial reinforcements (in the area of maximum stress) was similar to that of complete reinforcements, enabling a reduction in material usage by up to 60%. The thermal analysis (TGA) results demonstrated that glass fiber-reinforced composites exhibit high thermal stability, with mass loss starting at 320 °C and a residual mass of 8.02%; for other composite materials, thermal degradation begins at 305 °C, with a residual mass of 3.69%; in jute fiber-reinforced composites, thermal degradation starts at 300 °C, with a residual mass of 3.71%. SEM analysis generally revealed good fiber–matrix adhesion, while defects such as voids or detached fibers contributed to reduced mechanical strength. These results demonstrate that natural fiber-reinforced composite materials, particularly those reinforced with jute, can be used in sustainable engineering applications. They also show that localized reinforcement provides high performance with minimal resource consumption.